2013
DOI: 10.1517/14656566.2014.872241
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene receptor antagonists pranlukast and montelukast for treating asthma

Abstract: IntroductionThe prevalence of bronchial asthma, which is a chronic inflammatory disorder of the airway, is increasing worldwide. Although inhaled corticosteroids (ICS) play a central role in the treatment of asthma, they cannot achieve good control for all asthmatics and medications such as leukotriene receptor antagonists (LTRAs) with bronchodilatory and anti-inflammatory effects often serve as alternatives or add-on drugs. Several issues such as predicted responses, effects of peripheral airway and airway re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 100 publications
0
22
0
Order By: Relevance
“…In addition, cysteinyl LTs induce mucus secretion in vitro and in vivo [173, 174] and may also alter mucus viscosity [174]. Taken together, these effects implicated leukotrienes in the pathogenesis of pulmonary dysfunction, and after leukotriene synthesis inhibitors [175] and leukotriene receptor antagonists [176, 177] became available as drugs, anti-leukotriene therapy has been employed in the clinic to supplement glucocorticoid-base therapeutic schemes [178]. Nevertheless, as monotherapy, inhaled corticosteroids display superior efficacy to anti-leukotrienes in patients with persistent asthma and this superiority is particularly evident in patients with moderate airway obstruction [179].…”
Section: Biological Function Of Mammalian Lox Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cysteinyl LTs induce mucus secretion in vitro and in vivo [173, 174] and may also alter mucus viscosity [174]. Taken together, these effects implicated leukotrienes in the pathogenesis of pulmonary dysfunction, and after leukotriene synthesis inhibitors [175] and leukotriene receptor antagonists [176, 177] became available as drugs, anti-leukotriene therapy has been employed in the clinic to supplement glucocorticoid-base therapeutic schemes [178]. Nevertheless, as monotherapy, inhaled corticosteroids display superior efficacy to anti-leukotrienes in patients with persistent asthma and this superiority is particularly evident in patients with moderate airway obstruction [179].…”
Section: Biological Function Of Mammalian Lox Isoformsmentioning
confidence: 99%
“…On the other hand, it was suggested to limit anti-leukotriene therapy to asthmatics, who are refractory to inhaled corticosteroids or cannot use inhalant devices. Considering the low incidence of these circumstances oral anti-leukotrienes should be more carefully considered for treating asthma in the clinical environment but several clinically relevant issues (effects of anti-leukotriene medication on peripheral airways and on airway remodeling, alternative administration concepts) remain to be clarified before anti-leukotriene therapy could serve as a more effective strategy in the treatment of bronchial asthma in adults [177]. In children the beneficial effects of anti-leukotriene therapy for bronchial asthma are even more difficult to evaluate because the number and the size of clinical trials carried out so far is rather limited [182].…”
Section: Biological Function Of Mammalian Lox Isoformsmentioning
confidence: 99%
“…They induce airway constriction, bronchoalveolar mucus production and mucosal edema [17,18]. Two major cysteinyl leukotriene receptors (cysLTR1, cysLTR2) have been identified and antagonists at cysLTR1 (LUKASTs) are available for prescription as anti-asthmatics [19]. In contrast, the role of cysLTR2 still remains a matter of discussion [20].…”
Section: Leukotrienes: Classification Biosynthesis and Physiologicalmentioning
confidence: 99%
“…40 As a review reported, montelukast could replace ICS as first-line medications for asthmatic patients who are refractory to ICS or can not use inhalant devices. 41 Although prevention of asthma exacerbations has been identified in all asthma treatment guidelines, only in the past 10 years have exacerbations been used as a primary outcome variable in asthma. According to the recently published ATS/ERS statement, definitions of a mild or moderate asthma exacerbation are not justifiable.…”
Section: Discussionmentioning
confidence: 99%